Forgiveness and Reconciliation : Psychological Pathways to Conflict Transformation and Peace Building - Kalayjian, Ani (Springer, 2017)
Chapter 1: Introduction: Issues and Themes in Forgiveness and Reconciliation. Chapter 2: A Systemic Framework for Forgiveness, Reconciliation, and Peace: Interconnecting Psychological and Social Processes. Chapter 3: Forgiveness and Relational Ethics: The Perspective of the Contextual Therapist. Chapter 4: The Psychology of Forgiveness in the World Religions. Chapter 5: The Bullet and Its Meaning: Forgiveness, Nonforgiveness, and Their Confrontation. Chapter 6: Forgiveness and Reconciliation: Essential to Sustaining Human Development. Chapter 7: Art and Meaning:ARTiculation© as a Modality in Processing Forgiveness and Peace Consciousness. Chapter 8: Promoting Forgiveness Through Restorative Conferencing. Chapter 9: Guilt, Responsibility, and Forgiveness: Lessons from Lifers in Prison. Chapter 10: A Black Social Psychologist’s Perspective on Racial Forgiveness. Chapter 11: Rwanda: Repentance and Forgiveness – Pillars of Genuine Reconciliation. Chapter 12: Darfur: Efforts to Forgive and Reconcile in an Unresolved Conflict. Chapter 13: India and Pakistan on the Brink: Considerations for Truth, Reconciliation, and Forgiveness. Chapter 14: Forgiveness in the Context of the Armenian Experience. Chapter 15 Forgiveness in Spite of Denial, Revisionism, and Injustice Chapter 16 Reconciliation and Forgiveness in Divided Societies: A Path of Courage, Compassion, and Commitment. Chapter 17: Dialogue, Forgiveness, and Reconciliation.